Investigation and Characterization of materials towards building ionization vacuum gauges - Figueiredo, Ivo Guilherme Correia (2018)
Ionization gauge systems are one of the most frequent types of pressure measurement devices used for measuring very low pressures. In theory this type of devices could be used to measure extremely low pressures. However, when working in the lower end of the pressure range the ionization gauges suffer from stability issues leading to an increase in measurement uncertainty, which in turn limits the pressure work range. While the processes that influence the stability of these systems are fairly well known, not much has been done towards improving the actual systems. In line with the European EMPIR project “Towards a documentary standard for an ionization vacuum gauge”, this project aims towards proposing materials better suited for usage in regular ionization gauges. With that said, the project will focus on the study of one of the most pressing problems regarding the stability of the measurements made with ionization gauges, namely Ion Induced Secondary Electron Yield (IISEY) from ion collectors, by measuring the sample’s work function and surface degradation before and after exposure to environments similar to those present in ionization gauges and correlate them to measurements of the IISEY obtained mid exposure. Different candidate materials were chosen, namely molybdenum, gold and stainless steel. In all cases it became evident that carbon contamination is an inevitable occurrence in the collector electrode, even in clean environments. This contamination was deemed to originate from the material itself, in technical materials, and mainly from the filament and the grid electrode. In general, carbon content increase meant a decrease of IISEY. IISEY was deemed heavily influenced by surface conditions. As such, working with exotic species should provide adhesion of different compounds, therefore changing the IISEY. While not conclusive, stainless steel and gold seem to be the better suited of the candidate materials.